Designs and Discriminations for Clinical Group Supervision in Counselling Psychology: An Analysis - Grigg, Glen (Canadian Journal of Counselling and Psychotherapy, 2007)
Evidence suggests that group clinical supervision of counsellors and trainees is an effective mode of service delivery. However, clinical supervision is often understood to be concerned with teaching a generic set of skills. Without specifi cally labeling them as such, clinical supervision groups are implicitly identifi ed as psycho-educational groups. This article argues that such groups are better understood as counselling groups. The critique of existing group supervision strategies highlights the common use of small-group fixed-outcome strategies when a small-group fixed-process strategy is more appropriate to the task.